INNOVATION AND GROWTH : What Do We Know? - Thakor, Anjan V, (World Scientific, 2013)
This book, written entirely by faculty at the Olin Business School, Washington University in St. Louis, provides a variety of practical and implementable perspectives on innovation for managers. In addition, the book contains chapters that provide reviews of the academic research on innovation in the faculty members' specific areas of expertise. In taking this multifunctional approach to innovation, the focus of the book is not just on what is currently considered to be "best practice". Rather, it is on bringing to managers the cutting-edge knowledge that is being generated by academic research that goes beyond current best practice.